Isolation, characterization, and pathogenicity assessment of Corynebacterium pseudotuberculosis biovar equi strains from alpacas (Vicugna pacos) in China - Meng, Wanyu; Chen, Shanyu; Huang, Lin; Yang, Jinpeng; Zhang, Wenqing; Zhong, Zhijun; Zhou, Ziyao; Liu, Haifeng; Fu, Hualin; He, Tingmei; Peng, Guangneng (Frontiers in Microbiology, 2023)
Corynebacterium pseudotuberculosis is a zoonotic pathogen that causes lymphadenitis in humans, livestock, and wildlife. In this study, C. pseudotuberculosis biovar equi was successfully isolated from the extremity pus of diseased alpaca S2 and the liver abscess of dead alpacas (named G1 and BA3) and confirmed through biochemical tests and gene sequencing to corroborate the results. Antibiotic susceptibility tests showed that these three strains were resistant to aztreonam, fosfomycin, and nitrofurantoin. Pathogenicity tests showed that the median lethal dose (LD50) of strains G1, S2 and BA3 in experimentally infected mice was 1.66×10 5 CFU, 3.78×10 5 CFU and 3.78×10 5 CFU, respectively. DNBSEQ platform and the Oxford Nanopore technology were used to sequence strain G1, and Canu and GATK software were used to assemble the sequences. The final assembly was composed of a chromosomal scaffold of 2,379,166 bp (52.06% G+C content). The predicted gene functions in strain G1 revealed the presence of 48 virulence genes and 5 antibiotic resistance genes (ARGs). Comparative genomic analysis demonstrates a high degree of genetic similarity among C. pseudotuberculosis strains, in contrast to other Corynebacterium species, with a clear delineation between strains belonging to the two biovars (ovis and equi). The data of the present study contribute to a better understanding of the properties of C. pseudotuberculosis biovar equi strains and the 2 potential risk they pose to alpacas and other livestock, as well as the necessity of ongoing surveillance and monitoring of infectious diseases in animals.